Hubungan Antara Religiusitas Dengan Death Anxiety : Studi Meta Analisis - Muhammad Fakhrurrozi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
Meta analysis applied to 12 studies has proved that religiosity overall relate to death anxiety significantly. Intrinsic religious orientation, one of religiosity’s aspects has the biggest correlation coefficient than the four other aspects (r=-0-26). The following other four aspects are believe in life after death (r=0.1q97), ritual (r=0.149), the importance of religion (0.061) and stage of religion (r=-0.004). This meta analysis study findings shows that religiosity aspect is one of variables which has correlation to the death anxiety. Key words    :  death anxiety, religiusitas